Complementary Individualised Homoeopathy for Type-II Diabetics - A Randomised Controlled Study (Advancements in Homeopathic Research, 2022)
Background: Diabetes is a commonly encountered metabolic disorder worldwide. Numerous subjects suffer from diabetes. Role of homeopathy in diabetic subjects is not much explored. The present study was conducted to compare the effect of homeopathic medication as an additive to normal medications used by the subjects of type II diabetes mellitus. Materials and methods: The present prospective observational study was conducted in the department of homeopathy. The study was divided into two groups control group having only oral antidiabetic drugs and case group who were administered additional individualized homeopathic medicaments. The glycemic and blood profile was compared between the two groups. All the data was arranged in a tabulated form and analyzed statistically using SPSS software. Results: There were 61.5% males in case group and 56.9% in control group. The mean fasting blood glucose in the case and control group was 10.36+/-0.50 mmol/ L and 8.9+/-2.7 mmol/L respectively. At 6 months, the mean difference in the fasting blood glucose in the case and the control group was -2.25 and 0.14 respectively. There was a significant difference between the two as the p value was less than 0.05. Conclusion: The subjects taking homeopathic drugs showed significant improvement in the glycemic and lipid profile.
Keywords: diabetes; disorders; homeopathy; glycemic